(untitled) (Revista LIDER, 2020)
Through the development of diverse wine routes in Chile, a varied offer of enologic tourism has been generated, which has translated into changes in the local communities, since, the arrival of tourists has provoked an economic, social and cultural transformation of the environment and the lives of the inhabitants of the valleys of the center of Chile. Enologic tourism has not only implied costs, but benefits as well for the rural communities, such as improvement in infrastructure, broader offer of community services and greater job opportunities for all the inhabitants of the area, especially for the younger population. This study has the objectives to characterize the offer created by this type of tourism, to document the perception that the community of the valley of Colchagua, Chile has of the benefits generated by this tourism, and to identify the job opportunities rendered, especially to young people, and in what conditions. Among the most important results detected by the study are that enologic tourism has improved the availability of community services to render better treatment to toursists and it has generated a greater offer of employment opportunities in the area, though we detect weaknesses in the preparation of the employees in the sector.Asto the employment, we were able to determine that women have assumed an important role, and that though young people have contracts and benefits, they still expect job conditions to improve in the future.